Mitigating Distributed Denial of Service Attacks on IoT Systems Using Gemstone Architecture - Mohammad Robihul Mufid; Yogi Pratama; Arna Fariza; Saniyatul Mawaddah; Much Chafid; Agus Wibowo (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2025)
One of the problems in the Internet of Things (IoT) system is the Distributed Denial of Service (DDoS) attack on the information technology infrastructure on the Internet network. This is because the IoT device system does not have a portal gateway configuration that is capable of providing the necessary security and privacy protection. In this study, the focus is on the mechanism for reducing the impact of DDoS attacks of the http flood type on the layer framework using PHP Swoole. PHP Swoole utilizes event-driven which provides several features to access the transport layer in onConnect so that it can be used to implement initial security such as access control lists, connection concurrency management, and optimizing server performance. The methodology used is to develop a TCP connection filtering algorithm by implementing a simple queue system by accepting 67% of connections to be forwarded to the next layer and 33% of connections will be queued for a timeout of 2 seconds. The results of this study show that the server can minimize the impact of DDoS and handle traffic specifically for http requests with an average latency of 871.8ms.